Dampak Kebijakan Desentralisasi Terhadap Otonomi Daerah dalam Kerangka Hukum Tata Negara - Zaskia, Salwa; Br.Sembiring, Tamaulina; Harefa, Johan Berkat Fanolo; Zebua, M. Aulia Aditya Rahman (Innovative: Journal Of Social Science Research, 2025)
The decentralization policy implemented in Indonesia after the reformation is one of the strategic agendas within the framework of constitutional law reform, especially in terms of the relationship between the central and regional governments. Decentralization is intended to provide broader authority to regions to regulate and manage government affairs based on the principle of regional autonomy. In the context of constitutional law, this policy obtains constitutional legitimacy through Articles 18, 18A, and 18B of the 1945 Constitution of the Republic of Indonesia. However, in practice, the implementation of decentralization presents various problems, both in terms of inequality of authority, regional fiscal capacity, to the problem of supervision and accountability of regional government. Expanded regional autonomy is often not followed by institutional and human resource readiness in the regions, thus giving rise to disparities in development between regions. In addition, decentralization opens up opportunities for conflicts of interest, overlapping regulations between the center and regions, and weak coordination in the implementation of government. These various problems indicate the need to strengthen the constitutional law system that can strictly regulate the division of authority, supervision mechanisms, and harmonization of laws and regulations. Thus, it is hoped that decentralization will be able to run effectively and maintain the principle of a unitary state within the framework of the Unitary State of the Republic of Indonesia.